DESIGN OF A HOMESTAY AREA IN HUTA HIGH REGENCY OF SAMOSIR REGENCY BASED ON BATAK TOBA LOCAL WISDOM - Asido Martodi Simbolon; Ramadhani Fitri; Novalinda (Sean Institute, 2022)
Indonesia is a country known for its rich natural and cultural resources. One of the tourism sectors in North Sumatra is the Toba Batak culture. Where one aspect of culture in the Toba Batak reflects the potential for cultural tourism in Huta Tinggi, Samosir Regency. To develop and advance the potential of the tourism sector, especially in Huta Tinggi, Samosir Regency, and also as an effort to preserve culture, a Homestay building is needed which is one of the important factors in the development of the Homestay area in Huta Tinggi, Samosir Regency. local wisdom with a modern form (Neo-Vernacular) Toba Batak. This is because Neo-Vernacular Architecture shows a modern form but still has the image or characteristics of the area, but with a touch that is in accordance with the context of today. In the context of realizing the Samosir Regency Vision